Highly sensitive detection of CYFRA21-1 with a SERS sensing platform based on the MBs enrichment strategy and antibody-DNA-mediated CHA amplification - Bao, Xiaotao; Wang, Shiyi; Liu, Xiaoyan; Li, Guang (Frontiers in Bioengineering and Biotechnology, 2023)
Laryngeal carcinoma (LC) is the second most common malignant tumor of the head and neck. Due to its insidious nature, most patients have developed to the middle and late stages by the time they are diagnosed, missing the best treatment period. Thus, early detection, diagnosis and treatment are crucial to improve the prognosis of LC and enhance the quality of life of patients. In this study, a surface-enhanced Raman (SERS) sensing platform was developed by combining the magnetic beads (MBs) enrichment strategy and the antibody-DNA-mediated catalytic hairpin self-assembly (CHA) signal amplification technology. 4-Mercaptobenzoic acid (4-MBA) and hairpin DNA 1 (hpDNA1) were modified onto the surface of gold nanobipyramids (GNBPs) as SERS nanotags. Hairpin DNA 2 (hpDNA2) modified MBs were used as capture nanoprobes.Under the action of CHA and magnet-induced MBs enrichment, GNBPs can be assembled on the surface of MBs, forming high-density "hot spots" for the SERS signal enhancement. The results showed that the SERS sensing platform has the advantages of high sensitivity, high specificity and high reproducibility, with the limit of detection (LOD) low to pg/mL level. The expression level of CYFRA21-1 in serum of LC patients and healthy controls was successfully detected by the SERS sensing platform.The accuracy of the SERS results was verified by enzyme-linked immunosorbent assay (ELISA). Therefore, this SERS sensor can be used for the detection of CYFRA21-1 in serum, providing a simple and reliable new method for the early diagnosis of LC.